2019
DOI: 10.1021/acsaem.8b01793
|View full text |Cite
|
Sign up to set email alerts
|

Borane Incorporation in a Non-Fullerene Acceptor To Tune Steric and Electronic Properties and Improve Organic Solar Cell Performance

Abstract: Herein we study the effects of borane incorporation in a perylene diimide (PDI)-based non-fullerene acceptor (NFA). We have previously demonstrated that a PDI-bithiophene-PDI ((PDI) 2 Th 2 ) compound can be synthesized via direct (hetero)arylation techniques and is easily modified to incorporate a phosphole in the bithiophene core ((PDI) 2 Th 2 PO) to tune the electronic and geometric properties. In this work, we have synthesized the borane analogue ((PDI) 2 Th 2 B) and demonstrated that the organoboron moiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 100 publications
(226 reference statements)
0
31
0
Order By: Relevance
“…1 To promote more favorable phase separation in the BHJ, PDI self-assembly may be disrupted through either direct dimerization of PDIs [5][6][7] or insertion of a core between the PDI-moieties. [8][9][10][11][12][13][14][15][16][17][18][19] Fig. 1 Depicting previously investigated HOMO-modifying and newly synthesized LUMOmodifying N-annulated PDI-core-PDI materials.…”
Section: ▪ Introductionmentioning
confidence: 99%
“…1 To promote more favorable phase separation in the BHJ, PDI self-assembly may be disrupted through either direct dimerization of PDIs [5][6][7] or insertion of a core between the PDI-moieties. [8][9][10][11][12][13][14][15][16][17][18][19] Fig. 1 Depicting previously investigated HOMO-modifying and newly synthesized LUMOmodifying N-annulated PDI-core-PDI materials.…”
Section: ▪ Introductionmentioning
confidence: 99%
“…[11] Compared with the bithiophenec ore unit, the triarylborane core unit leads to decreased LUMO levels and improved electron mobility.W elch, Jäkle et al have reported a smallm olecule acceptorb ycombining at riarylboranec ore unit with perylenediimide units. [12] These studies suggestt hat the electron-deficientb orane core unit can be very effective in the design of novel small molecule acceptors for OSC applications.…”
Section: Introductionmentioning
confidence: 99%
“…Welch, Jäkle et al. have reported a small molecule acceptor by combining a triarylborane core unit with perylenediimide units . These studies suggest that the electron‐deficient borane core unit can be very effective in the design of novel small molecule acceptors for OSC applications.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Among all electron-accepting chromophores, boron(III)-containing moieties are anticipated to be promising candidates due to the vacant p-orbital on the boron center, making them inherently electron decient. [12][13][14] To date, a number of molecular NFAs using three-coordinate boranes or four-coordinate borates as electron-accepting chromophores for solutionprocessable OSCs have been reported in the literature; [15][16][17][18][19][20][21][22] however, only those NFAs containing double B ) N bridged bipyridine-based four-coordinate borates show PCEs exceeding 4%. 21,22 On the other hand, air-stable boron(III) b-diketonates, a family of classical four-coordinate borates, have proven to show strong luminescence, large extinction coefficients and nonlinear optical properties.…”
Section: Introductionmentioning
confidence: 99%